Ionic Conductiviy of Alginate-NH4Cl Polymer Electrolyte - Khan, Nurhasniza Mamajan; Ali, Noor Saadiah Mohd; Fuzlin, Ahmad Faizrin Ahmad; Samsudin, Ahmad Salihin (Makara Journal of Technology, 2020)
This study aims to produce a solid biopolymer electrolyte (SBE) by doping ammonium chloride (NH4Cl) into alginate. Solution casting was used to prepare the alginate–NH4Cl SBE system. Electrical impedance spectroscopy was performed to analyze the electrical properties of the SBE under the applied frequency range of 50 Hz–1 MHz. The incorporation of 8 wt.% NH4Cl enhances the ionic conductivity of the SBE up to 3.18 × 10-7 S/cm at ambient room temperature. Fourier transform infrared spectroscopy shows that complexation occurs between the hydroxyl (-OH), carboxylate (COO-) and ether linkage (C-O-C) functional groups due to the formation of inter- and intra-molecular hydrogen bonds between the biopolymer and the ionic dopant. The dielectric constant and dielectric loss increase with increasing dopant composition, thereby increasing the number of charge carriers and ionic mobility.